Cost implication of CPAP use in low resource settings, surmounting the oxygen administration challenge. (12th December 2022) - Okonkwo, Ikechukwu R.; Aneji, Chiamaka; Ekhaguere, Osayame A.; Eyo-Ita, Emmanuel U.; Okolo, Angela A.
Abstract: Purpose: Newborn respiratory support using Bubble Continuous positive airway pressure (bCPAP) has become acceptable in Nigeria as many centers are increasingly reporting its usefulness. There is increasing access to CPAP devices although the use of 100% oxygen for bCPAP administration is on the rise as oxygen/air blenders are not commonly available or insufficient. The cost of oxygen has become a significant contributor to hospital bills. The oxygen concentrator driven bCPAP device with blending capacity is expected to save lives and reduce cost of care. Objective: To compare the cost saving benefit of the use of oxygen concentrator bCPAP devices for CPAP administration to oxygen based devices in a resource limited setting. Methods: This prospective cross sectional study was done between February and December 2019. The oxygen use by CPAP devices-Improvised (IbCPAP), Fisher and Paykel and T-piece were quantified, costed, documented and compared with the same duration of use of concentrator CPAP-Diamedica. Results: CPAP services was accessed by 357 babies, 154 males and 203 females of GA range from 22 to 42 weeks and Birthweights range from 264 to 4400 grams. The main indication for CPAP was respiratory distress syndrome 201(56.3%). Oxygen supply were by oxygen pipeline 250 (70%), cylinders 39 (10.9%), concentrator CPAP 44 (12.3%) mixed source 24 (6.7%). Mean duration on the CPAP devices was 5.4 days, mean cost ₦37, 645 (104) or ₦6, 971 (20)/day, highest with IbCPAP, non-existent with concentrator bCPAP. Conclusion: The high running cost implication of CPAP use in low resource settings could deter transitioning to quality devices hence the need for non-oxygen dependent devices.